2022
DOI: 10.1007/s10765-022-03089-8
|View full text |Cite|
|
Sign up to set email alerts
|

Thermal Pressure in the Thermal Equation of State for Solid and a Proposed Substitute

Abstract: The thermal equation of state (TEOS) for solids is a mathematic model among pressure, temperature and density, and is essential for geophysical, geochemical, and other high pressure–temperature (high P–T) researches. However, in the last few decades, there has been a growing concern about the accuracy of the pressure scales of the calibrants, and efforts have been made to improve it by either introducing a reference standard or building new thermal pressure models. The existing thermal equation of state, P(V, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Thermal pressure represents a pressure change in isochoric heating, a measure of pressure change relative to the temperature at a constant volume. 100 Fig. 5(e) shows that the Ba 2 NaIO 6 structure has a low gradient monotonically increasing behavior of thermal pressure as a function of applied pressure.…”
Section: Resultsmentioning
confidence: 96%
“…Thermal pressure represents a pressure change in isochoric heating, a measure of pressure change relative to the temperature at a constant volume. 100 Fig. 5(e) shows that the Ba 2 NaIO 6 structure has a low gradient monotonically increasing behavior of thermal pressure as a function of applied pressure.…”
Section: Resultsmentioning
confidence: 96%
“…In paper [3,4], it was demonstrated that thermal expansion coe cient decreases with pressure in an isobaric heating process, which is not consistent with the assumptions in paper [1,2] of pressure independent of thermal expansion.…”
mentioning
confidence: 77%